bahasa inggris - Antonius Dian Kurnianto; Taufik Setyadi; Ida Syamsu Roidah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Shallots (Allium ascalonicum L.) are an important horticultural commodity in Indonesia, yet their high price volatility often causes disparities between farm-gate and retail prices. This condition indicates inefficiencies in the marketing system, long distribution chains, and weak bargaining power of farmers. This study examines the structure of shallot marketing channels, the distribution of marketing margins and farmers’ share, and the factors influencing shallot price formation at the retail level. The research aims to analyze marketing channel patterns, measure marketing margins and farmers’ share, and identify the main determinants of retail shallot prices in Jatirogo District, Tuban Regency, East Java. A mixed-method approach was applied, combining descriptive qualitative analysis with quantitative analysis using Partial Least Squares (PLS). Primary data were collected from 68 shallot retailers through interviews and structured questionnaires, supported by secondary data from official institutions and relevant literature. The results reveal three marketing channels with different efficiency levels. The farmer–consumer channel is the most efficient, with zero marketing margin and a farmers’ share of 100%, but it is limited in market reach. The farmer–collector–retailer channel generates a marketing margin of IDR 12,000/kg with a farmers’ share of 62%, while the farmer–collector–wholesaler–retailer channel records the highest margin of IDR 15,000/kg and the lowest farmers’ share at 57%. Furthermore, transportation costs, supply–demand imbalance, and marketing channel length significantly increase retail prices, while local production volume and substitute goods reduce prices. These findings highlight the importance of improving logistics efficiency and shortening marketing channels to enhance price stability and farmers’ income. Keywords: Shallot, Marketing Channels, Marketing Margin, Price Formation.